Correlation between dry density and shrinkage in eight tropical hardwood species - Adedeji Robert Ojo; Samson Oluwaseun Ogutuga; Lawrence Olanipekun Aguda (Les)
Eight tropical hardwood species were assessed for their density and radial, tangential and volumetric shrinkage, after which the relation between the density and different shrinkages was checked through correlation and regression. The results showed that the highest mean density was observed in Milicia excelsa with 900.63±50.13 kg/m³, followed by Afzelia africana, Nesogordonia kabingaensis and Nauclea diderichii with 831.25±41.67 kg/m³, 808.75±20.88 kg/m³ and 801.88±46.40 kg/m³, respectively. The mean density for Cassia simea was 781.88±27.71 kg/m³, Mansonia altissima 593.13±65.98 kg/m³, and Sterculia tragacantha 481.25±111.73 kg/m³, while the least density was observed in Treculia africana with 463.75±67.88 kg/m³. The highest volumetric shrinkage was observed in Nesogordonia kabingaensis with 14.71±2.28%, and the least in Cassia simea with 5.11±2.65%. It is concluded that there exists positive but weak correlation between density and the shrinkages in the eight tropical hardwood species.